Reverse coating technique for the production of Nb thin films on copper for superconducting radio-frequency applications. (1st December 2022) - Fonnesu, D; Baris, A; Calatroni, S; Lain Amador, L; Pfeiffer, S; Rosaz, G; Bonura, M; Senatore, C
Abstract: In the framework of the Future Circular Collider Study, the development of thin-film coated superconducting radio-frequency copper cavities capable of providing higher accelerating fields (10–20 MV m −1 against 5 MV m −1 for the Large Hadron Collider) represents a major challenge. The method investigated here for the production of seamless niobium-coated copper cavities is based on the electroforming of the copper structure around a sacrificial aluminium mandrel that is pre-coated with a niobium thin film. The first feasibility study, applied to a flat aluminium disk mandrel, is presented. Protective precautions are taken towards the functional niobium film during the production process and it is shown that this technique can deliver well performing niobium films on a seamless copper substrate. This way, the non-trivial chemical treatments foreseen by the standard procedures (e.g. SUBU, EP) for the preparation of the copper surface to achieve the proper adhesion of the niobium layer are also avoided. The only major chemical treatment involved in the reverse-coating method is represented by the chemical dissolution of the aluminium mandrel, which has the advantage of not affecting the copper substrate and therefore the copper-niobium interface.